Risk Factors for Sexual Offenses Committed by Men With or Without a Low IQ: An Exploratory Study - Vicenzutto, Audrey; Joyal, Christian C.; Telle, Émilie; Pham, Thierry H. (Frontiers in Psychiatry, 2022)
Although risk factors associated with offending and recidivism are relatively well established for mainstream sexual offenses, much less is known about men with a low IQ who have sexually offended (MIQSO), let alone those with forensic involvement. In this exploratory study, 137 men who have sexually offended were recruited in a maximum-security hospital and assessed with the SORAG (static risk factors) and the RSVP (dynamic risk factors). Compared with MIQSO (N = 76), men with an average or higher IQ who have sexually offended (MSO, N = 61) obtained significantly higher scores on static factors related with general delinquency (histories of alcohol abuse, non-violent criminality, violent criminality, and sexual offense) and dynamic factors related with sexual delinquency, paraphilia and recidivism (chronicity, psychological coercion, escalation, sexual deviance, and substance abuse). In contrast, MIQSO obtained significantly higher scores on major mental illness, problems with planning and problems with self-awareness. Logistic regressions revealed that both the SORAG and RSVP were useful to predict group membership. It is concluded that risk factors related with general and sexual delinquency better describe offenses committed by MSO, whereas risk factors related with mental disorder, lack of insight and contextual impulsivity better describe offenses committed by MIQSO.